An Optimization Path for Sb2(S,Se)3 Solar Cells to Achieve an Efficiency Exceeding 20% - Xiaoyong Xiong; Chao Ding; Bingfeng Jiang; Guanggen Zeng; Bing Li (Nanomaterials, 2024)
Antimony selenosulfide, denoted as Sb2(S,Se)3, has garnered attention as an eco-friendly semiconductor candidate for thin-film photovoltaics due to its light-absorbing properties. The power conversion efficiency (PCE) of Sb2(S,Se)3 solar cells has recently increased to 10.75%, but significant challenges persist, particularly in the areas of open-circuit voltage (Voc) losses and fill factor (FF) losses. This study delves into the theoretical relationship between Voc and FF, revealing that, under conditions of low Voc and FF, internal resistance has a more pronounced effect on FF compared to non-radiative recombination. To address Voc and FF losses effectively, a phased optimization strategy was devised and implemented, paving the way for Sb2(S,Se)3 solar cells with PCEs exceeding 20%. By optimizing internal resistance, the FF loss was reduced from 10.79% to 2.80%, increasing the PCE to 12.57%. Subsequently, modifying the band level at the interface resulted in an 18.75% increase in Voc, pushing the PCE above 15%. Furthermore, minimizing interface recombination reduced Voc loss to 0.45 V and FF loss to 0.96%, enabling the PCE to surpass 20%. Finally, by augmenting the absorber layer thickness to 600 nm, we fully utilized the light absorption potential of Sb2(S,Se)3, achieving an unprecedented PCE of 26.77%. This study pinpoints the key factors affecting Voc and FF losses in Sb2(S,Se)3 solar cells and outlines an optimization pathway that markedly improves device efficiency, providing a valuable reference for further development of high-performance photovoltaic applications.